2019
DOI: 10.2131/jts.44.327
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms underlying transcriptional induction of metallothionein isoforms by tris(pentafluorophenyl)stibane, tris(pentafluorophenyl)arsane, and tris(pentafluorophenyl)phosphane in cultured bovine aortic endothelial cells

Abstract: -Metallothionein (MT) is a low-molecular-weight, cysteine-rich, and metal-binding protein that protects cells from the cytotoxic effects of heavy metals and reactive oxygen species. Previously, we found that transcriptional induction of endothelial MT-1A was mediated by not only the metal-regulatory transcription factor 1 (MTF-1)-metal responsive element (MRE) pathway but also the nuclear factor-erythroid 2-related factor 2 (Nrf2)-antioxidant response element/electrophile responsive element (ARE) pathway, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Deletion of Nrf2 suppressed the ZnO-NP-induced increase in metallothionein-1 but increased the background level of metallothionein-2 expression. Metallothionein-1 and -2 are known to be regulated by metal response element (MRE), but recent studies show transcriptional induction of metallothionein-1 thorough Nrf2 /ARE pathway [5153], which might partly explain the suppression of ZnO-NP-induced increase in metallothionein-1. Metallothioneins are cysteine-rich and heavy metal-binding proteins known to contribute to a wide range of protective cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Nrf2 suppressed the ZnO-NP-induced increase in metallothionein-1 but increased the background level of metallothionein-2 expression. Metallothionein-1 and -2 are known to be regulated by metal response element (MRE), but recent studies show transcriptional induction of metallothionein-1 thorough Nrf2 /ARE pathway [5153], which might partly explain the suppression of ZnO-NP-induced increase in metallothionein-1. Metallothioneins are cysteine-rich and heavy metal-binding proteins known to contribute to a wide range of protective cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…Cu10 has been found to induce endothelial metallothionein, a cytoprotective protein. Subsequent studies using this copper complex have revealed that metallothionein induction is mediated by different intracellular signaling pathways for different metallothionein isoforms [20][21][22]. Proteoglycans synthesized by vascular endothelial cells play important roles in regulating the growth factor/cytokine activity [23] and blood-coagulation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nobuhiro Kajihara et al found that low glucose conditions exacerbated mtROS production through activation of fatty acid oxidation in bovine aortic endothelial cells [18]. Other researchers have also used cattle as their own experimental models [19][20][21][22][23][24]. We used the GSE75240 dataset to show that gut microbes can change the expression of proteins or genes in the blood.…”
Section: Discussionmentioning
confidence: 99%